Time Variant Password Okamoto–Uchiyama Cryptography based Three Layer Authentication for Secured Financial Transaction - Ruba, N.; Khadir, A. Shaik Abdul (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Cloud computing enabled customers to save data on a cloud server for scalable services. The Internet of Things (IoT) provides a virtual representation for physical objects in order to share data and adapt to environmental changes with efficient resource utilization. IoT include distributed sensor nodes to gather cloud user information from different location through wireless medium. A financial transaction represents the exchange of goods, services, or assets for payment and serves as a form of communication between the buyer and seller. Different authentication methods are introduced by existing researchers for performing efficient secured financial transaction. However, there was no enhancement in authentication accuracy, and the authentication time remained unimproved. In order to address these issues, an IoT framework with three layer authentication called Time Variant Password Okamoto–Uchiyama Cryptography based Three Layer Authentication (TVPOUC-TLA) Method is introduced. The main aim of TVPOUC-TLA Method is to perform IoT based efficient financial transaction with higher confidentiality rate. TVPOUC-TLA Method covers four steps, which are crucial generation, encryption, authentication and decryption for taming the safety level performance in cloud environment. In the TVPOUC-TLA Method, a cloud user located in a different location (acting as the buyer) initiates the registration process with the cloud server (acting as the seller) to facilitate authentication. During the strategic key generation phase, the Cloud Server (CS) generates both the public and private keys for the registered cloud user. Whenever a cloud user needs to perform any financial transaction, cloud user gets logged in with help of key pair and transmits the demand note to the CS. Later getting request, CS confirms the cloud manipulator authenticity through sending the time variant password and fingerprint. When the cloud user pass in password and fingerprint acquires matched with CS sent password, cloud manipulator has said to be an authorized user and accomplish financial transaction. Otherwise, the transaction between cloud server and cloud user gets declined. This approach enables the efficient and secure execution of financial transactions through the TVPOUC-TLA Method. An experimental assessment is conducted, focusing on factors including authentication accuracy, data confidentiality rates, and data integrity, taking into account variations in the number of financial data entries and cloud users.